THE CONSUMER ACCEPTANCE ON SMOKE FLAVOURED CATFISH SAUSAGE (Clarias gariepinus) - Sukandar, Titieu Keumala; Ilza, Mirna; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the research was to determine the consumer acceptance on the smoke flavoured catfish sausage. This research was conducted in 2 steps, those were the production of coconut shell redistilled liquid smoke and the production of smoke flavoured catfish sausage. The method used was the experimental composed as non factorial Randomized Complitely Design. The treatment factor was addition of liquid smoke in the catfish sausage, consisted of 4 levels, namely addition of 0 mL (SA0), 2 mL (SA2), 4 mL (SA4), and 6 mL (SA6) for every 315 g fish meat each. The result showed that the catfish sausage added with 2 ml liquid smoke in (SA2) was indicated as the highest sensory value. The proximate composition indicated that the lowest water content was shown on the catfish sausage added with 4 ml liquid smoke (SA4) amounting to 7,01% meanwhile the highest one was SA0 amounting to 7,58 %. The highest content of protein was SA2 amounting to 30,25% and lowest one was SA6 amounting to 24,56%. The highest content of fat was SA4 amounting to 2,31% and lowest one was SA0 amounting to 1,28%. The highest content of ash was SA6 amounting to 4,00% and lowest one was SA0 amounting to 2,21% and the highest content of phenol was SA6 amounting to 12,29% and lowest one was SA0 amounting to 0,41%. Keywords : consumer acceptance, fish sausage, liquid smoke, Clarias gariepinus